A comparison of airway dimensions, measured by acoustic reflectometry and ultrasound before and after general anaesthesia. (14th August 2014) - Ushiroda, J.; Inoue, S.; Kirita, T.; Kawaguchi, M.
Summary Changes in airway dimensions can occur during general anaesthesia and surgery for a variety of reasons. This study explored factors associated with postoperative changes in airway dimensions. Patient airway volume was measured by acoustic reflectometory and neck muscle diameter by ultrasound echography in the pre‐ and post‐anaesthetic periods in a total of 281 patients. Neck circumference was also assessed during these periods. A significant decrease in median (IQR [range]) total airway volume (from 63.8 (51.8–75.7 [14.7–103]) ml to 45.9 (33.5–57.2 [6.4–96.3]) ml, p < 0.0001), and a significant increase in muscle diameter (from 4.3 (3.3–5.6 [2.2–9.0]) mm to 5.8 (4.7–7.3 [2.8–1.3]) mm, p < 0.0001) and neck circumference (from 34.0 (32.5–37.0 [29.5–49.0]) cm to 35.0 (33.5–38.0 [30.5–50.5]) cm, p < 0.0001) were observed. It may be possible that changes in airway volume and neck circumference were influenced by surgical duration or peri‐operative fluid management (ρ) = −0.31 (95% CI −0.24 to −0.01), p = 0.0301, −0.17 (−0.23 to −0.06), p = 0.0038, 0.23 (0.12–0.34), p < 0.0001, and 0.16 (0.05–0.27), p = 0.0062, respectively). The intra‐oral space can significantly decrease and neck thickness increase after general anaesthesia, and might increase the risk of difficult laryngoscopy and intubation if airway management is required after extubation following general anaesthesia.